Planar Printed Shorted Monopole Antenna with Coupled Feed for LTE/WWAN Mobile Handset Applications - Do-Gu Kang; Youngje Sung (International Journal of Antennas and Propagation)
A shorted monopole antenna with coupled feed for LTE/WWAN mobile handset applications is described. The basic resonance of the shorted monopole combines with the resonance formed by the coupling between the coupling strip and the feeding pad to cover the LTE700, GSM850, and GSM900 bands. Both the feeding pad and the coupling strip operate with the shorting strip as a loop antenna. The resonance of the loop antenna and the harmonics of the shorted monopole combine to cover the GSM1800, GSM1900, UMTS, and LTE2300 bands. A stable and omnidirectional radiation pattern with reasonable gain has been observed over the operating bandwidth.